2008
DOI: 10.1007/s10549-008-0105-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of infiltrating lymphocytes and estrogen receptor on gene expression and prognosis in breast cancer

Abstract: The involvement of the immune system for the course of breast cancer, as evidenced by varying degrees of lymphocyte infiltration (LI) into the tumor is still poorly understood. The aim of this study was to evaluate the prognostic value of LI in breast cancer samples using microarray-based screening for LI-associated genes. Starting from the observation that most published ER gene signatures are heavily influenced by the LI effect, we developed and applied a novel approach to dissect molecular signatures. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 40 publications
9
83
1
1
Order By: Relevance
“…LAMP3 expression in breast cancer xenografts colocalizes with tumor cell hypoxia as revealed by pimonidazole labeling. Together with our immunohistochemical data on actual breast tumors, this indicates that lymphocyte infiltration, which reportedly has different effects on prognosis in breast cancer depending on ER status, 23 is unlikely to be the sole cause of the association of LAMP3 mRNA with prognosis we report here. Rather, the tumor epithelial cells themselves aberrantly express LAMP3, with consequences for locoregional control.…”
Section: Discussionsupporting
confidence: 75%
“…LAMP3 expression in breast cancer xenografts colocalizes with tumor cell hypoxia as revealed by pimonidazole labeling. Together with our immunohistochemical data on actual breast tumors, this indicates that lymphocyte infiltration, which reportedly has different effects on prognosis in breast cancer depending on ER status, 23 is unlikely to be the sole cause of the association of LAMP3 mRNA with prognosis we report here. Rather, the tumor epithelial cells themselves aberrantly express LAMP3, with consequences for locoregional control.…”
Section: Discussionsupporting
confidence: 75%
“…This observation raises the question of whether cancer-immune hotspot co-localization is a feature of the microenvironment that provides organspecific niche for successful metastasis. [31][32][33] Notably, a weak correlation was found between the degree of cancer and immune hotspot co-localization and immune abundance, a parameter of clinical significance reported by us and other groups 7,10,12 who showed that a high immune abundance is correlated with better survival outcome in ER-negative breast cancer. We were able to demonstrate that our hotspot score can further stratify patients with high immune abundance.…”
Section: Modern Pathology (2015) 766-777mentioning
confidence: 69%
“…6 Methods to assess tumoral immune infiltration include traditional pathological examination and gene expression profiling. 7,8 Although the latter can indicate the immune cell type and their relative abundance, a more comprehensive analysis of their number, lineage and spatial distribution requires pathological assessment. [9][10][11][12] Spatial information on the tumor immune microenvironment is of clinical relevance, as not only the abundance and type but also the spatial locations of immune cells have been shown to be associated with clinical outcome in colorectal 13 and breast cancer.…”
mentioning
confidence: 99%
“…18,29,30 Therefore, although a number of gene expression signatures have been published revealing high levels of molecular heterogeneity in immune infiltration, [31][32][33][34] pathological assessment remains critical for discerning tumor spatial heterogeneity. Lymphocytes can be identified based on their typical morphology of small, round and homogeneously basophilic nuclei which differentiates them from other leukocytes, such as neutrophils with more elongated and segmented nuclei.…”
Section: Immune Cellsmentioning
confidence: 99%